Activation of NLRP3 inflammasome in macrophages by mycoplasmal lipoproteins and lipopeptides. (29th May 2018) - Saeki, A.; Sugiyama, M.; Hasebe, A.; Suzuki, T.; Shibata, K.
Summary: The NLRP3 inflammasome, an intracellular sensor consisting of the nucleotide‐binding oligomerization domain‐like receptor family, pyrin domain containing 3 (NLRP3), the adaptor protein apoptosis‐associated speck‐like protein containing a caspase‐recruitment domain (ASC), and procaspase‐1, plays critical roles in host defense against microbial pathogens by inducing production of interleukin‐1β (IL‐1β) and IL‐18. Mycoplasma salivarium and Mycoplasma pneumoniae cells activated murine bone marrow‐derived macrophages (BMMs) to induce production of IL‐1α, IL‐1β, and IL‐18. The IL‐1β production‐inducing activities of these mycoplasmas toward BMMs from Toll‐like receptor 2 (TLR2)‐deficient mice were significantly attenuated compared with those from C57BL/6 mice (B6BMMs). This result suggests the possibility that their lipoproteins as TLR2 agonists are involved in the activity. Lipoproteins of M. salivarium and M. pneumoniae (MsLP and MpLP), and the M. salivarium ‐derived lipopeptide FSL‐1 induced IL‐1β production by B6BMMs, but not by BMMs from caspase‐1‐, NLRP3‐ or ASC‐deficient mice. The activities of MsLP and MpLP were not downregulated by the proteinase K treatment, suggesting that the active sites are their N‐terminal lipopeptide moieties. B6BMMs internalized the mycoplasmal N‐terminal lipopeptide FSL‐1 at least 30 min after incubation, FSL‐1‐containing endosomes started to fuse with the lysosomes around 2 hours, and then FSL‐1 translocated into the cytosol from LAMP‐1 + endosomes. The artificial delivery of FSL‐1 into the cytosol of B6BMMs drastically enhanced the IL‐1β production‐inducing activity. FSL‐1 as well as the representative NLRP3 inflammasome activator nigericin induced the NLRP3/ASC speck, but FSL‐1 located in a compartment different from the NLRP3/ASC speck.